2021
DOI: 10.1155/2021/5471347
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polyphenols as Antioxidant Supplementation in Ischemic Stroke

Abstract: Stroke is the second most common cause of death globally and the leading cause of death in China. The pathogenesis of cerebral ischemia injury is complex, and oxidative stress plays an important role in the fundamental pathologic progression of cerebral damage in ischemic stroke. Previous studies have preliminarily confirmed that oxidative stress should be a potential therapeutic target and antioxidant as a treatment strategy for ischemic stroke. Emerging experimental studies have demonstrated that polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 159 publications
(160 reference statements)
0
17
0
Order By: Relevance
“…Dioscin could be hydrolyzed to diosgenin in mammalian body, and diosgenin could not be further metabolized ( Li et al, 2019 ). Traditional Chinese medicine provides direction for research on functional foods and natural products based on abundant clinical practices ( Zhou et al, 2021a ; Zhou et al, 2021b ). Yam, usually applied to treat digestive system diseases, reminds researchers of the potential function of diosgenin in metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Dioscin could be hydrolyzed to diosgenin in mammalian body, and diosgenin could not be further metabolized ( Li et al, 2019 ). Traditional Chinese medicine provides direction for research on functional foods and natural products based on abundant clinical practices ( Zhou et al, 2021a ; Zhou et al, 2021b ). Yam, usually applied to treat digestive system diseases, reminds researchers of the potential function of diosgenin in metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that inflammation, excitatory toxicity, iron accumulation and oxidative stress occur during the onset of stroke [107]. The use of iron chelating agents, antioxidants, and free radical scavengers can reduce cerebrovascular damage after stroke [108,109]. Recent studies have found that hippocampal neurons in vitro stroke models and mouse cortical nerve cells after ischemia and reperfusion in vivo have the characteristics of ferroptosis, and the use of ferroptosis inhibitors can significantly reverse cell death [77,110].…”
Section: Strokementioning
confidence: 99%
“…Natural polyphenols are mainly found in fruits and vegetables, nuts, soybeans, tea, cocoa, and alcohol. Polyphenols are known as “the seventh category of nutrients” and have antioxidant effects [ 91 ]. As shown in Table 1 , phenolic compounds could attenuate the oxidative stress caused by ICH.…”
Section: Targeted Therapy Of Oxidative Stress With Natural Productsmentioning
confidence: 99%